Bankfull discharge estimation for Fishpot Creek - Sakhaee, Farhad (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Abstract: Fishpot Creek has been investigated and bankfull discharge was calculated based on the collected data points obtained from 3D laser scanning of the stream. This report consists of two major parts. One is the 3D scanning and analysis the results, other part includes sampling of both bed and bank materials. In the first part, essential parameters of roughness coefficient based on Cowan’s method were calculated as well as calculating the cross-sectional area and wetted perimeter based on the profile obtained from stream channel scanning. Leica Scan Station HDS 3000 scanner was used to visualize the cross-sectional shape of the stream based on a high-density scan technology and finally applied to the manning’s equation to calculate the bankfull discharge. for sampling part both bed and bank materials were analyzed in lab, mechanical sieve test performed to investigate the gradation of bed and banks materials within the study area.